Answer:
![(A-2wh)/(2(w+h))=l](https://img.qammunity.org/2022/formulas/mathematics/college/5ftesbaf132fwb1qfw6oym1wm9yob0j3ua.png)
Explanation:
We have to find the formula for the value of 'l'.
So, we will isolate 'l' on one side of the formula.
A = 2lw + 2lh + 2wh
A = 2l(w + h) + 2wh
A - 2wh = 2l(w + h) + 2wh - 2wh
A - 2wh = 2l(w + h)
![(A-2wh)/(2(w+h))=(2l(w+h))/(2(w+h))](https://img.qammunity.org/2022/formulas/mathematics/college/do4uyq1i0fyaia5n44cypyuvysau77zgd3.png)
![(A-2wh)/(2(w+h))=l](https://img.qammunity.org/2022/formulas/mathematics/college/5ftesbaf132fwb1qfw6oym1wm9yob0j3ua.png)
Therefore, formula for 'l' will be,
![(A-2wh)/(2(w+h))=l](https://img.qammunity.org/2022/formulas/mathematics/college/5ftesbaf132fwb1qfw6oym1wm9yob0j3ua.png)